Global optimization using nonparametric filled function method - Goh Khang Wen (Fakulti Sains dan Teknologi, 2011)
Mathematicians believe some of the daily problem that we faced can be modeled into mathematical model. There are several unconstrained optimization methods which have been developed in order to solve those mathematical models. However, they often failed in locating the global solution of non-convex optimization problems. Hence, the main purpose of this research is to improve the ability of the existing local deterministic method in solving unconstrained general deterministic global optimization problems.